Efektifitas Pembelajaran Kelas Ibu Hamil dalam Menurunkan Anemia di Kecamatan Grogol Sukoharjo - Nur Agustiningsih; Muwakhidah . (Universitas Muhammadiyah Semarang, 2018)
Maternal deaths in developing countries one of the causes is anemia in pregnancy, an increasing proportion of pregnant women with anemia. One effort to prevent and overcome the occurrence of anemia in pregnant women is maternal class program which aims to increase knowledgeand skill of mothers about pregnancy, childbirth, postpartum care and newborn care, through practice by using KIA book ( Child Mother Health). The purpose of this study is to determine the effectivenessof learning systems of pregnant mothers class in reducing of anemia in the District Grogol Sukoharjo District. This type of research is Quasi-Exsperimental Design, using Non Equivalent Control Group Design. Sampling by Consecutive sampling technique with the number of 40 respondents for each group.Measure of hemoglobin level using cyanmethemoglobin, andstattistic analysis using MannWhitneytest. The result showed that the average of maternal and non maternalclass knowledge was 86.9 + 76.5, the mean of anemia onmaternal and non maternal class was 11.9 g/dl and 11.2 g/dl.Based on the result of statistical test, there is difference of knowledge between maternal and nonmaternal class (p = 0,000), and there is difference of anemia between maternal and non maternal class(p = 0,001). The conclusion of riset was there is difference of knowledge and anemia between maternaland maternal class. Keywords : maternal class, Anemia